1980
DOI: 10.1080/03079458008418409
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related resistance to Avian Leukosis virus I. Influence of age at exposure on mortality and congenital transmission

Abstract: Groups of White Leghorn chickens were inoculated at 1 day and at 2, 4, 6 and 8 weeks of age respectively with a mixture of leukosis viruses of subgroups A and B. The five infected groups were kept in a filtered air positive pressure house. A sixth group was accommodated separately in a similar house as a control. All birds which died or were removed were subjected to pathohistological examination; diagnosis of lymphoid leukosis was made upon either gross lesions plus microscopical lesions or microscopical lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…The chicks of groups 1, 3, 4, 5 and 6 were derived from a spf White Leghorn strain A parent flock of the Central Veterinary Institute (Maas et al, 1980). The chickens of groups 2, 7 and 8 originated from a flock of the same strain of chickens present in the flocks participating in our experimental LL control programme.…”
Section: Experimental Chickens and Holding Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chicks of groups 1, 3, 4, 5 and 6 were derived from a spf White Leghorn strain A parent flock of the Central Veterinary Institute (Maas et al, 1980). The chickens of groups 2, 7 and 8 originated from a flock of the same strain of chickens present in the flocks participating in our experimental LL control programme.…”
Section: Experimental Chickens and Holding Conditionsmentioning
confidence: 99%
“…The procedures and criteria for pathological examination have been described previously (Maas et al, 1980).…”
Section: Pathologymentioning
confidence: 99%
“…There are several ways in which this might be brought about. Maas et al (1980) have reported that the occurrence of vertical transmission following horizontal infection is agerelated: infection by LLV before 4-8 weeks of age (by injection) results in congenital transmission, whereas infection at 8 weeks does not. Differences in response to contact infection are apparently not so clear although it seems likely that there would be a similar trend (Weyl and Dougherty, 1977).…”
Section: Theory Of Vertical Transmissionmentioning
confidence: 99%
“…Burmester (Regional Poultry Research Laboratory, East Lansing, U.S.A.) in 1967. The second strain, the WL strain A, developed as a leukosis virus-free flock (Maas et al, 1980), was at that time of unknown susceptibility to MD. From the WL line 7 2 ,50 out of 100 one-dayold chicks were placed in an isolation unit, and inoculated intra-abdominally with strain K MDV and the remainder served as contact controls (penmates).…”
Section: Experimental Planmentioning
confidence: 99%